Leucocortinarius brunnescens (Agaricales), a new species from southwestern China - He, Jin-Fu; Cai, Qing; Fan, Xue-Ping; Yang, Zhu L. (Phytotaxa, 2024)
Leucocortinarius has long been regarded as a monotypic genus, with only one species, L. bulbiger, which was originally described from Europe. However, a new species of the genus, namely L. brunnescens, is described from southwestern China based on morphological characteristics, molecular phylogenetic evidence, and ecological traits. This species is very similar to L. bulbiger but differs from the latter by its lamellae becoming dark brown to blackish when dried, smaller basidiospores, and different DNA sequences.